University Education Quality and Academic Citizenship Behaviour: the Mediating Role of Student Loyalty - Cao, Mengyu (Journal of Positive Management, 2025)
This study investigates the relationship between university education quality and student loyalty and academic citizenship behaviours in Polish public universities. This study extends to the current literature by viewing students as essential members of academic institutions rather than just customers, resulting in a more complex understanding of student-institution interactions. Survey data from a variety of business majors show a substantial positive relationship between perceived education quality and both student loyalty and academic citizenship behaviours, with loyalty mediating the relationship. These findings highlight the significance of quality-oriented university strategies in fostering student loyalty and encouraging academic citizenship behaviours, implying that institutions may benefit from recognising students as valued academic community members rather than simply as consumers of educational services.